Strategi Pembangunan Spiritual Nabi Muhammad pada Masa Awal Madinah - Kusuma Haren, Niken (STID Al-Hadid, 2023)
SPIRITUAL EMPOWEREMENT STRATEGY OF PROPHET MUHAMMAD IN THE EARLY TIME OF MADINAH. The Prophet Muhammad made the people of Medina have an Islamic value from the background of differences between groups in the formation of society. Spiritual empowerment is a fundamental effort made by the Prophet Muhammad by implementing the right strategy. This article aims to describe the spiritual empowerment strategy carried out by the Prophet Muhammad in the early days of Medina. The theory used is based on the community development strategy according to Adi and the forms of empowerment stages according to Suharto and the types of empowerment described by Mardikanto and Soebianto which are then classified based on the method, form, and target of the empowerment strategy. The method used is a qualitative historical literature in order to describe the historical events of the Prophet Muhammad from the data obtained. The results of the study show that the strategy applied by the Prophet Muhammad in the spiritual field is in the form of enabling and strengthening because the community is still in the early stages of development so that they can apply an Islamic value consistently. It is carried out by means of a directive in the process of determining the strategy but still being non-directive in the implementation of the strategy, or in a prophetic strategy combining two approaches, namely a directive-non-directive strategy. And targets that are mezzo and macro, with the position that the prophet also has as a leader who has been trusted by the community. From this strategy, it can solve the problems that the community has, especially in the spiritual field. eld.